Creating a Diploma Supplement Linked to Degree-Awarding Policies When the Curriculum Comprises Mostly of Elective Subjects - Yoshioka Tsuyoshi; Teruya Kensaku (Journal of Management Practices, Humanities and Social Sciences, 2020)
This study aims at defining a remodeled adjusted value for Learning Degree value Graph (LDG) and proposing a method to recalculate the Learning Degree (LD). The Diploma Supplement (DS) is an attachment to a degree certificate that enhances transparency by clearly indicating the contents acquired. DS for a curriculum mostly is comprised of electives and cannot fairly represent student abilities. This study uses a DS creation method linked to degree-awarding policies—commonly called "Diploma Policies" (DP) in Japan. Specifically, each subject is associated with a plurality of DP items and a student's contribution rate in a subject (subject learning rate) is set based on the contents of the DP items. The DS is created by multiplying the number of acquired credits by the subject learning rate of each DP and the learning evaluation level as the learning degree of each DP item. If all students are taking the same subjects, then a fair DS can be created by this method by calculating the LD. As a result, a method for creating a DS linked to DPs that accurately represents student abilities even when the curriculum is mostly composed of electives is successfully developed. This method could be helpful as the DS here reflects a fair evaluation of student's degree regardless of the subjects studied.